TINJAUAN PREFERENSI PELARI TERHADAP PENGGUNAAN MUSIK SAAT JOGGING - tama, utama irvan abdi; nuridin widya pranoto; wilda welis; Fahmil Haris; Rina Mayangsari (Jurnal IKEOR, 2026)
This study stems from the problem that many recreational runners experience boredom, decreased motivation, and inconsistency while Jogging, so music is used as a stimulus to improve comfort and performance. This study aims to review runners' preferences regarding the use of music while Jogging, including running habits, preferred types of music, purposes of use, and perceived impacts. The study used a descriptive quantitative method with an accidental sampling technique on 50 runners aged 17–40 years at the Haji Agus Salim Sports Hall, Padang. Data were collected using a five-point Likert-scale questionnaire and analyzed using percentages for each indicator. The results showed that the majority of runners jog regularly and are accustomed to using music to support their activities. Fast-tempo music with motivating lyrics is the dominant choice. Music has been shown to increase enthusiasm, focus, comfort, mood, and improve self-confidence, duration, and Jogging performance. Most respondents also have favorite songs and special playlists while running. The study's conclusions confirm that music plays an important role in supporting the Jogging experience, both psychologically and physiologically. Individual music preferences also influence the motivation and effectiveness of running activities, so music can be used as a strategy to improve the quality of Jogging activities.